Reductive clean leaching process of cadmium from hydrometallurgical zinc neutral leaching residue using sulfur dioxide. (1st February 2016) - Zhang, Chun; Min, Xiaobo; Zhang, Jianqiang; Wang, Mi; Li, Yuancheng; Fei, Jiangchi
Abstract: Large quantities of cadmium-containing zinc neutral leaching residues (ZNLR) are produced constantly in the electrolytic production of zinc, creating serious cadmium pollution. In order to solve the problem and realize a clean zinc production process, a new reductive cleaning leaching process using sulfur dioxide as reducing agent has been developed, in which the beneficiation of cadmium pollution factor is solved. The cadmium leaching mechanisms were briefly analyzed and the effects of temperature, initial sulfuric acid and partial pressure of sulfur dioxide on the kinetics of cadmium dissolution in the mixed SO2 +H2 SO4 system was investigated. The order of reaction with respect to particle size, initial sulfuric acid concentration and partial pressure of sulfur dioxide at the fixed liquid/solid ratio and stirring speed were determined as −0.98, 1.49 and 0.51, respectively. Diffraction peak of zinc ferrite or cadmium-bearing zinc ferrite disappeared and the main compositions of the reductive leaching residue were lead sulfate (PbSO4 ), zinc sulfide (ZnS) according to the XRD analysis. Highlights: Cadmium mainly exists as cadmium-bearing zinc ferrite in zinc residue. Reductive leaching of Cd in the presence of SO2 was found to be highly effective. H + plays a key role during the reductive decomposition of the ferrite. PbSO4 is the main constituent of the reductive leaching residue.